Modulation of helix stability of indolocarbazole–pyridine hybrid foldamers. Issue 16 (1st February 2016) - Kim, Jee Seon; Jeon, Hae-Geun; Jeong, Kyu-Sung
Abstract : The kinetic stabilities of the helical conformations of indolocarbazole–pyridine hybrid foldamers were modulated through single site modification. Abstract : Through variation of the central pyridine in an indolocarbazole–pyridine hybrid foldamer, the kinetic stabilities of helical conformations were determined and compared based on the inter-conversion rates of P and M helical isomers.